Gambaran Pengetahuan tentang Pencabutan Gigi pada Remaja - Juliatri, Juliatri; Mariati, Ni Wayan; Simanjuntak, Bintang (Universitas Sam Ratulangi, 2025)
Abstract: Knowledge about tooth extraction can help teenagers to understand the importance of maintaining dental health and preventing more serious dental problems in the future. This study aimed to obtain the overview of level of knowledge about tooth extraction among adolescents. This was a descriptive study with a cross-sectional design. Sampling technique was stratified proportionate random sampling. Samples consisted of 175 students of SMP Katolik Santa Theresia (junior high school) Manado obtained by using the Slovin formula. The results showed that from 175 students, 52% had very good level of knowledge, 32.8% had good knowledge, and 21.2% had poor knowledge. Number of female respondents that had very good level of knowledge was higher than of male respondents (53,2% : 51%). Elder respondents had higher level of knowledge compared to the younger ones. In conclusion, the number of students having very good level of knowledge is higher than those having good level and poor level of knowledge. Female students have higher level of knowledge than male students, and elder students have higher level of knowledge compared to the younger ones. Keywords: knowledge about tooth extraction; adolescence Abstrak: Pengetahuan tentang pencabutan gigi dapat membantu remaja memahami pentingnya menjaga kesehatan gigi dan mencegah masalah gigi yang lebih serius di masa depan. Penelitian ini bertujuan untuk mendapatkan gambaran pengetahuan tentang pencabutan gigi pada remaja. Jenis penelitian ialah deskriptif dengan desain potong lintang. Teknik pengambilan sampel yaitu stratified proportionate random sampling. Sampel berjumlah 175 siswa SMP Katolik Santa Theresia Manado yang diperoleh menggunakan rumus Slovin. Hasil penelitian mendapatkan bahwa sebanyak 52% siswa memiliki tingkat pengetahuan sangat baik, 32,8% memiliki pengetahuan baik, dan 21,2% memiliki pengetahuan kurang baik. Responden perempuan (53,2%) yang memiliki tingkat pengetahuan sangat baik lebih banyak daripada responden laki-laki (51%). Responden yang berusia lebih tua memiliki tingkat pengetahuan yang lebih baik dibandingkan yang berusia lebih muda. Simpulan penelitian ini ialah siswa yang memiliki tingkat pengetahuan sangat baik lebih banyak dibandingkan dengan yang memiliki tingkat pengetahuan baik dan kurang baik. Siswa perempuan memiliki tingkat pengetahuan yang lebih baik dibandingkan laki-laki, dan siswa yang berusia lebih tua memiliki tingkat pengetahuan yang lebih baik. Kata kunci: pengetahuan mengenai pencabutan gigi; remaja